Complete nucleotide sequence and polypeptide analysis of multicomponent phenol hydroxylase from Pseudomonas sp. strain CF600. - Nordlund, I (1990)
Pseudomonas sp. strain CF600 metabolizes phenol and some of its methylated derivatives via a plasmid-encoded phenol hydroxylase and meta-cleavage pathway. The genes encoding the multicomponent phenol hydroxylase of this strain are located within a 5.5-kb SacI-NruI fragment. We report the nucleotide sequence and the polypeptide products of this 5.5-kb region. A combination of deletion analysis, expression of subfragments in tac expression vectors, and identification of polypeptide products in maxicells was used to demonstrate that the polypeptides observed are produced from the six open reading frames identified in the sequence. Expression of phenol hydroxylase activity in a laboratory Pseudomonas strain allows growth on phenol, owing to expression of this enzyme and the chromosomally encoded ortho-cleavage pathway. This system, in conjunction with six plasmids that each expressed all but one of the polypeptides, was used to demonstrate that all six polypeptides are required for growth on phenol.